Étude de l'emploi des peintures thermochromiques dans l'Art contemporain - Marjorie Nastro (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This study on the use of thermochromic paintings is based on Véronique Joumard’s artwork Mur – tableau (vert), conceived and made in 2004. This research was led as a graduation project at Avignon’s Superior Art School  in collaboration with the laboratory of Chemistry applied to Art and Archeology (university of Avignon), GEM’INNOV and MINOLTA Ets. It focuses on the  physico-chimical features of “Thermosensitive” colors.